An Assessment of Physicochemical Parameters of Selected Industrial Effluents in Nepal - Abhinay Man Shrestha; Sanjila Neupane; Gunjan Bisht (Journal of Chemistry)
It is a well-known fact that the effluents released from the industries and environmental degradation go hand in hand. With the ongoing global industrialization this problem has been further aggravated. As such, Nepal is no exception. Hundreds of industries are being registered in the country annually which inevitably brings the issues regarding environmental pollution. This study has been conducted with samples of wastewater from 5 different industrial sites in 4 districts of Nepal, namely, Makwanpur, Sunsari, Morang, and Kathmandu, among which two were Waste Water Treatment Plants which treated the combined effluents collected from various sources. The other three sites were from wires and cables industry, paint manufacturing industry, and plastic cutting industry. The physicochemical parameters analysed were pH, temperature, conductivity, turbidity, and Cu, Cr, SO42-, and PO43- levels. Possible onsite measurements were recorded using portable, handheld devices whereas other parameters were assessed in the laboratory. The observed parameter levels in the collected samples were compared against the available Nepal national standards for industrial effluents and in the absence of standards for industrial effluents, with other relevant standard levels. Most of the parameters analysed were within the permissible limits with the exception of pH and Cr levels in some sites.